Understanding the mental calculus of a victim advisor: a survey experiment in the context of college campus sexual victimization - Burton, Alexander L. (Psychology, crime & law, 2025)
This study examines factors that weigh on a victim advisor’s mental calculus when approving whether a victim report a crime to the police. A factorial design was embedded in a survey of college students (n = 1221) and vignettes randomized the relationships between the victim, advisor, and perpetrator and the age of the victim and perpetrator. Results indicate that relationships between parties significantly weigh on an advisors’ mental calculus of approving a crime be reported. Moreover, advisors disapprove reporting if the perpetrator is a juvenile and they approve reporting if the victim is a juvenile. Advisors’ personal biases also mattered.